KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI - Solikhin, Agus (Manajemen & Bisnis Jurnal, 2018)
The purpose of this study is to examine the effect of simultaneous and partial competence and career development on the performance of Sekolah Tinggi Pariwisata Sahid Surakarta Employees. The population of this study is the population in this study were all Sekolah Tinggi Pariwisata Sahid Surakarta employees, with a research sample of 95 employees. The analytical tool used is multiple regression. The results showed that competency and career development simultaneously and partially had a significant effect on the performance of Sekolah Tinggi Pariwisata Sahid Surakarta Employees. The results of this study can be used as an evaluation in developing human resources to support the improvement of competencies by providing opportunities to participate in trainings that support their work and formulate career development regulations Keywords: Competence, Career Development and Employee Performance